2017
DOI: 10.20473/ijtid.v6i4.3806
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Activity of Copper(ii)chloride Dihydrate Against Dengue Virus Type-2 in Vero Cell

Abstract: Infection of dengue virus (DENV) was number of globally significant emerging pathogen. Antiviral dengue therapies are importantly needed to control emerging dengue. Dengue virus (DENV) is mosquito-borne arboviruses responsible for causing acute systemic diseases and grievous health conditions in humans. To date, there is no clinically approved dengue vaccine or antiviral for humans, even though there have been great efforts towards this end. Copper and copper compounds have more effective in inactivation virus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 22 publications
0
28
0
Order By: Relevance
“…17 The effects of other compounds against cellular RNA polymerases and formation of the complex with RNA have reported suggesting that compound could also affect the similar replication enzymes. 18 Previous research was reported anti-dengue type 2 activity, especially Cu(II) with 2,4,5-triphenylimidazole exhibited adsorption inhibitory activity at IC 50 = 2.3 μg/ml. 11 A significant inhibitory activity to that of the complex Co(II) with 2-(2,4-dihydroxyphenyl)-3,5,7trihydroxycromen -4-one ligand was reported against the tested pathogenic dengue virus type 2 in Vero cells 3.08 μg/ ml.…”
Section: Anti-dengue Type 2 Virus Activitymentioning
confidence: 95%
“…17 The effects of other compounds against cellular RNA polymerases and formation of the complex with RNA have reported suggesting that compound could also affect the similar replication enzymes. 18 Previous research was reported anti-dengue type 2 activity, especially Cu(II) with 2,4,5-triphenylimidazole exhibited adsorption inhibitory activity at IC 50 = 2.3 μg/ml. 11 A significant inhibitory activity to that of the complex Co(II) with 2-(2,4-dihydroxyphenyl)-3,5,7trihydroxycromen -4-one ligand was reported against the tested pathogenic dengue virus type 2 in Vero cells 3.08 μg/ ml.…”
Section: Anti-dengue Type 2 Virus Activitymentioning
confidence: 95%
“…13 When compared with a previous study, it has been revealed that Co(II) is more toxic than Cu(II) with a CC 50 value of 5.03 µg/ml. 18 Copper(II) was found to be nontoxic to human erythrocyte cells even at a concentration of 500 µg/ml. 20 …”
Section: Antiviral Activity Of Cobalt(ii)-morinmentioning
confidence: 98%
“…The sI of the antiviral compound appeared to be moderately influenced by the strain of DENV tested. 18 The emergence of arboviruses worldwide raises the necessity of developing a new strategy for the treatment of the diseases they cause. several approaches have been demonstrated for the treatment of DENV-2 in which Cobalt(II)-Morin at concentrations of micrograms per milliliter promote inactivation.…”
Section: Antiviral Activity Of Cobalt(ii)-morinmentioning
confidence: 99%
“…Specifically, the use of copper salt nanoparticles and/or solutions (chloride, iodide, sulfide, etc. ), which are known for having an antiviral effect [54][55][56][57][58], could be helpful in the development of PPE with improved shielding properties. As an example, the treatment of non-woven overshoes, surgical gowns, hair cups, respirators, etc.…”
Section: Antiviral Drug Virus Infection Action Mechanism Referencesmentioning
confidence: 99%